Unwritten Scars: Gaslighting in Relationships - Licia Kurniawan; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Gaslighting is a modern term that describes a type of toxic relationship that psychologically abuses the victim. Gaslighting is understood as manipulating the victim into questioning his sanity and the gaslighter has a goal to create a ‘surreal’ environment that will cause the victim to feel like he is in the wrong and is crazy. Since gaslighting is all about manipulation, it can cause mental disorders. In the theoretical framework, we will apply the concept of gaslighting and self-actualization to show the effects of gaslighting and the ways to cope with it. In this work, we explore how gaslighting can cause anxiety, depression and low self-esteem in the victims. We show that the victims of gaslighting can deal with it by fulfilling physiological needs and building herself up again by the help of friends and families. Keywords: gaslighting, toxic relationship, poetry, lyrical poem